Uji Potensi Bakteri Endofit Kitinolitik Tanaman Padi (Oryza sativa L.) Sebagai Penghasil Hormon IAA (Indole Acetic Acid) - Hanafi, Ahmad; Purwantisari, Susiana; Raharjo, Budi (Bioma : Berkala Ilmiah Biologi, 2017)
IAA (Indole Acetic Acid) is a hormone in plants that was role in the cleavage of roots, inhibits the growth of side shoots, stimulate cell division and the formation of xylem and phloem tissue. This study aimed to test the potential of endophytic bacteria chitinolytic rice crop as hormone-producing IAA. This study uses 9 isolates of endophytic bacteria chitinolytic rice plants in isolation during practical work. The experiment consisted of 15 treatments and 3 replications. This study uses a randomized block design. The treatments tryptophan concentration combined with a variation pH, the endophytic bacteria grown on media chitinolytic tryptophan concentration of 0 mg/L, 102 mg/L, 204 mg/L, 306 mg/L and 408 mg/L are combined with pH 5, 7 and 9. the treatment was observed for 48 hours and observation once every 3 hours. The measured variable is the result of the production of IAA hormone with the treatment combination of tryptophan with pH. IAA hormone outcome data were analyzed using Analysis of Variance Univariates at level of 95%. IAA hormone qualitative test results showed positive results in bacterial isolates KA12, KA11 and KB24. IAA hormone quantitative results of bacterial isolates producing IAA hormone KA12 high of 2,03 mg/L in the combination treatment of tryptophan 408 mg/L at pH 7 at 24 hours incubation. KA12 bacterial isolates are endophytic bacteria chitinolytic potential to produce hormones IAA, yet the results of data analysis showed that each treatment combination with pH tryptophan to IAA production were not significantly different.Â Keywords: hormone IAA, chitinolytic endophytic bacteria, tryptophan, pH